Evaluasi Potensi Wisata Alam Pulau Lemukutan Kabupaten Bengkayang, Kalimantan Barat - RULIYANSYAH, AGUS (Jurnal Arsitektur Lansekap, 2016)
ABSTRACT Evaluation of Potential Ecotourism Lemukutan Island Bengkayang District, West Kalimantan Lemukutan Island, Bengkayang, West Kalimantan, has the potential of ecotourism that is very nice. The aims of this study was to evaluate the potential contained in the island tourist Lemukutan to be the basis of sustainable ecotourism management. Some of the potential in the form of beaches, coral reefs, rock promontory, smallholder and seafood. Activities supporting facilities like water supply, transportation and lodging need to be equipped and upgraded. Tourism development must consider biophysical nature so that ecotourism Lemukutan Island can be sustainable. Keywords: Bengkayang District, ecotourism, Lemungkutan island